The Language of Publications on the Impact of Robotisation on Labour - Zbozień, Monika (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Objective: The aim of this paper is to verify the language used in publications on the impact of robotisation on labour.Research Design & Methods: The analysis covered ten articles on the impact of robots on labour published between 2015–2018. The focus is on the most frequently used words.Findings: The most frequently discussed challenges concern income distribution and income polarisation. The industry most exposed to the impact of robots is production, routine work, physical work and professions performed by less-educated people.Implications / Recommendations: The results suggest that income distribution and income polarisation are the biggest challenges related to the impact of robotisation on labour.Contribution: The article identifies current and potential future directions in research related to the impact of robotisation on labour.